1967
DOI: 10.1039/j19670000561
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric studies on solubilisation in non-ionic micellar solutions. Part II. Solubilisation of benzoic acid and the hydroxybenzoic acids and location of the solubilisates

Abstract: Previous studies on the solubilisation of benzoic acid by aqueous solutions of the polyoxyethylene glycol monoalkyl ether (C, H, , & + ,.[OCH,*CH,];OH)Cetomacrogol (n = 16, m = 24) have been extended to the hydroxybenzoic acids in the same system, and to benzoic acid in glycol monoethers of the ranges 1 n = 12, m = 9, 16, and 20; n = 16, m = 20, 24, and 60. The results all fit the form of the Langmuir isotherm, indicating that solubilisation involves binding to definite sites in the system; this is interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The reported K ad value for 2-nitrodiphenylamine adsorbed onto polystyrene-b-poly(acrylic acid) micelles was 5.7 Â 10 5 L/mol, whereas values of 7 to 34 L/mol were obtained with salicylic acid and benzoic acid adsorbing onto polyoxyethylene glycol monoalkyl ether micelles. 24,25 As expected, great variability in adsorption constants can be found depending on the properties of the substrate and adsorbate. Pyrene in CrEL and NOF did not fit the Langmuir adsorption isotherm model with correlation coefficients of 0.30 and 0.07, respectively (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The reported K ad value for 2-nitrodiphenylamine adsorbed onto polystyrene-b-poly(acrylic acid) micelles was 5.7 Â 10 5 L/mol, whereas values of 7 to 34 L/mol were obtained with salicylic acid and benzoic acid adsorbing onto polyoxyethylene glycol monoalkyl ether micelles. 24,25 As expected, great variability in adsorption constants can be found depending on the properties of the substrate and adsorbate. Pyrene in CrEL and NOF did not fit the Langmuir adsorption isotherm model with correlation coefficients of 0.30 and 0.07, respectively (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…19,20 There are specific examples in which authors have described the interaction of small molecules with surfactant micelles as a binding phenomenon and have fit the data to a Langmuir isotherm. [21][22][23][24] Choucair and Eisenberg describe the binding of 2-nitrodiphenylamine at the core-corona interface of polystyrene-b-poly(acrylic acid) micelles, and find that the best fit is through the Langmuir binding isotherm. 25 The binding of the preservative parahydroxybenzoic acid esters to polysorbate 80 micelles has been described as Langmuir-like.…”
Section: Resultsmentioning
confidence: 99%
“…The binding isotherms were measured using equilibrium dialysis, but unfortunately the data were presented only graphically, and furthermore in the Freund]ich form (i.e., log r versus log a) rather than being analyzed according to the Langmuir form (correspond-ing to simple site-binding) to which these types of systems in many cases conform (49). Nevertheless, the Freundlich isotherms, which were all essentially linear, show a fairly regular shift to lower concentrations with alkyl chain length, suggesting that there is a correspondingly regular increase in the strength of binding.…”
Section: Comparison Of the Present Results For P Vp With Previous Stumentioning
confidence: 99%
“…The critical micelle concentration of commonly used non-ionic surfactants is sufficiently low for the monomer concentration to be neglected. Equation (6) has the same form as the Langmuir equation which has led some authors to suggest that the mechanism of interaction between solute and surfactant is one of adsorption onto the surface of the micelle or some other site within the micelle (Donbrow & Rhodes, 1964;Donbrow, Molyneux & Rhodes, 1967). However, as pointed out by Goldstein (1949) and Klotz (1953) for solute-protein interaction, although the equations are similar it is not necessarily correct to assume that binding and adsorption are identical processes.…”
Section: Interaction As a "Binding" Phenomenonmentioning
confidence: 89%
“…It cannot be assumed that the value of K m obtained from equation (3) will be applicable to under-saturated systems. Moreover it has been shown that the solubilization process of benzoic acid is not governed by the distribution law (Donbrow & Rhodes, 1964;Donbrow, Molyneux & Rhodes, 1967;Donbrow, Azaz & Hamburger, 1970). …”
Section: Interaction As a Partition Phenomenonmentioning
confidence: 99%